2019
DOI: 10.5089/9781484398074.001
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Community Based Health Insurance Schemes on Out-of-Pocket Healthcare Spending: Evidence from Rwanda

Abstract: IMF Working Papers describe research in progress by the author(s) and are published to elicit comments and to encourage debate. The views expressed in IMF Working Papers are those of the author(s) and do not necessarily represent the views of the IMF, its Executive Board, or IMF management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Willingness to pay means the maximum (non-zero) amount that households are willing to pay for the insurance scheme, elicited through a double bounded contingent valuation method specifically by applying a bidding game. 8,22 The wealth index questionnaire was adapted from Ethiopian Health Insurance Agency on the number and kinds of consumer goods they own, housing characteristics, and availability of basic amenities for residents. 28 From these, scores were derived using principal component analysis and were classified into five quintiles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Willingness to pay means the maximum (non-zero) amount that households are willing to pay for the insurance scheme, elicited through a double bounded contingent valuation method specifically by applying a bidding game. 8,22 The wealth index questionnaire was adapted from Ethiopian Health Insurance Agency on the number and kinds of consumer goods they own, housing characteristics, and availability of basic amenities for residents. 28 From these, scores were derived using principal component analysis and were classified into five quintiles.…”
Section: Methodsmentioning
confidence: 99%
“…7 Among the prepaid mechanisms, health insurances improve access to quality health-care services, protecting households from health-related financial risks, and ultimately improving the health status of the poor. 8 Of these, community-based health insurance (CBHI) is one means of pooling risks across different population groups so that it significantly reduces the financial burden of catastrophic illnesses for individuals. 9 CBHI reduces direct out-ofpocket payment at the point of service delivery and improves cost recovery, though its effect on crosssubsidy is questionable.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of persons with MD, aside from the availability of strategies to prevent CHE, mechanisms of access for protecting households from health-related financial risks are not widely available, as has been reported in the literature (Woldemichael et al ., 2019 ). Moreover, there is a disparity between medical attention provided to the population for physical health and attention provided for mental health (Lavie-Ajayi et al ., 2018 ), due in part to the extent of poverty, the segmentation and fragmentation of the health system, and the lack or unequal distribution of financial, physical, and human resources in the health system (Laurell, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding gives more support to our results, in the sense that these households face adverse social conditions such as lower formal education, lower probability to have formal and well-paid employment, and consequently have lower income. In this context, it is notable that in the present study, we found that household income level was a major determinant of the probability of CHC, and similar results have been reported in other studies (Zuvekas and Selden, 2010 ; Rezaei and Hajizadeh, 2019 ; Tirgil et al ., 2019 ; Woldemichael et al ., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taxes and health insurance are the means recommended by the WHO to raise funds for the health sector in low and middle-income countries in order to achieve UHC (including financial risk protection) [ 2 , 6 ]. Taxes and health insurance have shown good results in other African countries such as Ghana and Rwanda providing increased financial risk protection and increased service utilization [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%